KARAKTERISTIK DAN MAKNA TERITORI TERAS RUMAH BERLABUH MASYARAKAT SERUI ANSUS (Studi Kasus permukiman rumah berlabuh masyarakat Serui Ansus Kota Sorong, Papua Barat) - Sahambangun, Devy Sarah; Soukotta, Dwars (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2021)
Terrace is a transitional space into the house in general which functions as a waiting room or a place to relax. However, at the rumah berlabuh settlement of Serui Ansus community, the terrace has more functionality than the lounge or waiting room because the houses are above sea level. The terrace functions as a central point for many activities. The shape of the territory as an area for different activities is an interesting point for further research. Â This builds upon the research of the Community Settlement Pattern of Serui Ansus (2014). This study Used a qualitative descriptive method, the data used is the result of case study observations with a sign language approach and open interviews in case studies on rumah berlabuh settlements of the Serui Ansus community in Klademak 2 Village, Sorong City. The results of this study indicate that the pattern of coastal settlements built on water forms a pattern of activities that occur on the space terrace with various activities, which form the characteristics and meaning of the terraced territorial spaces in the Serui Ansus settlement. There are 3 characteristics of the terrace shape with 3 models of boundary patterns with different meanings. Some of the terraces in some case studies are primary territories, but there are terraces that are secondary territories or are used by a group of people for socializing.Â